Studi Kelayakan Bisnis Umkm Kota Tangerang (Studi Kasus Usaha Soto Daging Sapi “Mbah Man” Kondang Rasa) - Fardillah, Frena; Zahrowain, Muhammad Yushiy (Journal Industrial Manufacturing, 2023)
UMKM Soto Beef "Mbah Man" Kondang Rasa is one of the MSMEs in Tangerang City engaged in culinary. In business development, it is necessary to analyze the feasibility of investment with a financial aspect approach and technical feasibility with a technical aspect approach which will ultimately produce an assessment or decision whether this business should be developed or not. Data collection method with direct observation and interview and data processing by tabulating data that refers to the calculation of aspects of investment feasibility analysis, namely Net Present Value (NPV), Payback Period (PP), Internal Rate of Return (IRR), and Profitability Index (PI) as well as technical aspect approach analysis. The results of the technical aspect approach are declared feasible in determining the location, layout and  readiness of machines, the best inventory methods, and the need for labor. Meanwhile, the feasibility from the financial aspect shows that the business is feasible to run with eligibility criteria that produce  a Payback Period (PP) for 2 months 27 days, a Net Present Value (NPV) value of IDR 1,285,373,578, an Internal Rate of Return (IRR) value of 7.68% >  7% (interest rates), and a Profitability Index (PI) value of 14.60 >1 Keywords: MSMEs, Business Feasibility, Financial Aspects, Technical Aspects